Mediators of innate and adaptive immune responses differentially affect immune restoration disease associated with Mycobacterium tuberculosis in HIV patients beginning antiretroviral therapy - Oliver, B.; Elliott, J.; Price, Patricia; Phillips, M.; Saphonn, V.; Vun, M.; Kaldor, J.; Cooper, D.; French, M. (Oxford University Press, 2010)
Background. Initiation of antiretroviral therapy (ART) in human immunodeficiency virus patients with treated or unrecognized Mycobacterium tuberculosis infection may result in tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) or ART-associated tuberculosis (ART-TB), respectively. Both conditions appear to be immune restoration disease but their immunopathogenesis is not completely understood. Methods. Chemokines and cytokines produced by the innate immune system (CCL2, CXCL8, CXCL9, CXCL10, and interleukin 18 [IL-18]) were assayed in plasma from unstimulated whole blood cultures obtained from 15 TB-IRIS case patients, 11 ART-TB case patients, and matched control participants over 24 weeks of ART. Results. When compared with control participants, levels of IL-18 and CXCL10 were higher in TB-IRIS case patients (P = .002 and .006, respectively), whereas CCL2 was lower (P = .006). IL-18 level was higher in ART-TB case patients (P = .002), but CXCL10 was only marginally higher (P = .06). When TB-IRIS case patients were compared with ART-TB case patients, IL-18 was higher in ART-TB (P = .03), whereas CXCL10 was higher in TB-IRIS (P = .001). Using receiver operating characteristic curves, pre-ART levels of CCL2, CXCL10, and IL-18 were predictive of TB-IRIS and additive to IFN-? responses. Conclusions. Perturbations of the innate immune response to M. tuberculosis before and during ART may contribute to the immunopathology of TB-IRIS, whereas elevated IL-18 alone suggests adaptive immune responses predominate in ART-TB. These findings may have implications for therapy in TB-IRIS. © 2010 by the Infectious Diseases Society of America. All rights reserved.